(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In order to manage the speed of brushless DC (BLDC) motors, this research presents a novel hybrid control method that simultaneously regulates the DC bus voltage of the inverter and the BLDC motor reference current. A fractional-order PID (FOPID) controller manages the BLDC motor reference current, and a fuzzy logic controller manages the inverter DC bus voltage. A modified harmony search (HS) metaheuristic technique is developed for adjusting the FOPID controller parameters. Three separate working scenarios—no load, varying load, and varying speed—are used to test the motor’s capabilities. Run the proposed controller at a high speed to verify its efficacy. The suggested hybrid control method has also been put to the test. weighed against FOPID and fuzzy-based speed control techniques The outcomes demonstrate the effectiveness of the suggested control. approach enables more accurate speed control over a wide region.